Children’s Self-Regulation in Cultural Contexts: The Role of Parental Socialization Theories, Goals, and Practices - Jaramillo, Jorge M.; Rendón, María I.; Muñoz, Lorena; Weis, Mirjam; Trommsdorff, Gisela (Frontiers in Psychology, 2017)
Self-regulation is a complex multidimensional construct which has been approached mainly in Western cultural contexts. The present contribution examines the importance of considering the culture-sensitive nature of self-regulation by reviewing theory and research on the development of children’s self-regulation in different cultural contexts. This review of theory and research allows to suggest that widely shared values in a cultural group influence parental socialization theories, goals and practices, which in turn have an impact on how children learn to self-regulate, the forms of self-regulation they develop, and the goals associated with self-regulation. Thus, this article concludes that more specific research is required to relate both the developmental and the cultural aspects of children’s self-regulation.